Etodolac adsorption onto activated carbon prepared by chemical activation and pyrolysis of biomasses mixture - Erdem, Hatice; Yildiz, Burcin; Sahin, Mehmet; Erdem, Mehmet (Springer Heidelberg, 2020)
In this study, a novel microporous activated carbon (AC) from low-cost biomasses (apricot and peach stones, and almond shell) mixture by FeSO4 activation and following pyrolysis was synthesized, characterized, and tested for etodolac (ETD) adsorption. The characteristics of AC were determined by BET surface area, total pore volume, average pore size, surface functional group analysis by Boehm's titration and FTIR, and SEM-EDX. A high-quality activated carbon with 958.57 m(2)/g surface area, 0.4796 cm(3)/g total pore volume, and 1.9963-nm average pore size could be successfully synthesized from the mixture activated by FeSO4 at impregnation ratio of (FeSO4/precursor (w/w)) 0.5. ETD adsorption ability of the prepared AC was investigated depending on the effects of AC dosage, contact time, pH, initial ETD concentration, and temperature. Also, the linear and nonlinear forms of Langmuir and Freundlich isotherms and pseudo-first-order and pseudo-second-order kinetic models were compared to get the best isotherm and kinetic model. The results showed that more than 95% ETD adsorption could be achieved at the presence of 5 g/L of AC, contact time of 150 min, and at a wide pH range. The adsorption data was found to be best fitted to the nonlinear pseudo-second-order kinetic model and nonlinear Freundlich isotherm. The adsorption of ETD onto the AC was found to be exothermic and spontaneous.
Keywords: Activated carbon; Adsorption; Biomass; Characterization; Etodolac; Synthesis